Predictors of persistent post transplant hyperparathyroidism (HPTx) - Ulisses, Luiz Roberto Sousa; Camargo, Leonardo Figueiredo; Sousa, Marcos Vinícius de; Vale, Carla Feitosa do; Rivelli, Gabriel Giollo; Mazzali, Marilda (Brazilian Journal of Transplantation, 2015)
Post transplant persistent Hyperparathyroidism (HPTx) increases the risk for transplant complications. Purpose: to identify risk factors for HPTx in the first post transplant year. Methods: Retrospective analysis of medical records from renal transplant recipients from July/2008 to December/2010. Inclusion criteria: serum PTH ≥500 pg/ml at transplant and normal 1-year graft function (serum creatinine ≤ 2mg/dL). From a group of 224 renal transplants, 69 (30%) fulfilled the inclusion criteria, and they were divided in 2 groups, according to the serum PTH after 1 year of transplant: control, 1-year P TH<150 p g/ml ( n=32) a nd P ersistent H yperparathyroidism, H PTx, 1 -year P TH ≥ 1 50 p g/ml ( n= 3 7). Data analyzed: serum calcium (Ca), phosphate (Pi), alkaline phosphatase (AP), PTH and glomerular filtration rate (GFR) at transplant, and 3, 6 and 12 months post transplant. Results: At transplant, the groups were comparable as to age, Pi and PTH. However, the length of the dialysis (78 40 vs. 50 34 months, p<0.05) and Ca (8,9 0.9 vs. 8,5 0,6mg/dL, p<0.05) were higher in the HPTx group. After 3 months post transplant, HPTx group maintained higher PTH levels (365.4 176.2 vs. 166.9 92.2pg/mL, p<0.05), and AP (175 145 vs. 109 52UI, p<0.05), than controls, despite of the comparable Ca, Pi, and GFR. From the 6th post transplant month, the HPTx group persisted with hypercalcemia (10.2 0.7 vs. 9.9 0.5mg/dL, p<0.05) and low phosphate (2.6 0.5 vs. 2.9 0.7, p<0.05) with higher AP and PTH levels than in controls (p<0.05). At the end of the 1 post transplant year, HPTx group persisted with hypercalcemia, despite the recovery of the graft function while in the control group, the GFR recovery was associated with normalization of the bone mineral metabolism parameters. Conclusion: HPTx was associated with longer pre transplant dialysis therapy and higher Ca at transplant. Higher PTH and AP post transplant levels at the 3rd month were associated with persistent hyperparathyroidism, as well as persistent hypercalcemia and low phosphate, despite of the GFR recovery.